Eksistensi Komisi Pengawas Persaingan Usaha dalam Penanganan Persekongkolan Tender dalam Perspektif Hukum Positif Indonesia - Surya Bhakti; Zainal Asikin; Sahnan Sahnan (Faculty of Social Science, Universitas Negeri Padang, 2020)
This study aimed to examine and analyze the legal position of the the Supervision Commission as the only institution dealing with competition law in Indonesia legal system and determine the existence of law enforcement of the Commission as the only institution related to tender collusion (conspiracy) viewed from the Indonesian legal perspective. This was a normative study (research), with a statutory and conceptual approach. The results of this study indicated that the position of the Supervision Commission as the only institution dealing with competition law in Indonesia in the justice system was independent from the influence of other institutions in resolving disputes on unfair business competition in Indonesia; and the existence of the Commission is the only institution dealing with competition law in Indonesia in carrying out its duties and authorities in accordance with the mandate of the Law Number 5 of 1999 concerning the prohibition of monopolistic practices and unfair business competition.